Effect of antipsychotic on the dimension of auditory hallucination among patients with schizophrenia - Ismail, Norhajar; Wahab, Suzaily; Mat Zin, Nora (IIUM Press, 2025)
INTRODUCTION: Auditory hallucination (AH) is the most common type of hallucinations in individuals with schizophrenia. Assessing the multidimensional aspects of AH provides more precise insights, particularly regarding associated psychological sequelae. This study aimed to examine the short-term effects of antipsychotics treatment on the emotional, cognitive and physical dimension of AH.